PENINGKATAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN DISCOVERY LEARNING PADA SISWA KELAS VII SMP NEGERI 5 ABIANSEMAL - Ni Luh Sintya Dewi (LPPM Universitas Bina Bangsa, 2023)
To achieve educational success, one of the elements is the teacher who plays a very important role in the teaching and learning process (Rahayu, et al., 2018). Mathematics is one of the basic subjects at every level of formal education which plays a very important role. Mathematics is a basic science needed to prepare competent human resources with integrity. However, in reality, mathematics lessons are often considered difficult by students and boring, so there is a need for learning models that attract students' attention so that they are active in learning and learning becomes fun. One of them is the Discovery Learning learning model. Discovery Learning is a learning method that focuses on discovering previously unknown concepts or principles and solving problems followed by validating abilities so that it is hoped that students will be able to improve their thinking skills and find solutions to problems (Fatmawati, 2016). Discovery Learning encourages students to take responsibility for their learning process so they can more easily transfer their knowledge to various contexts and feel empowered. As a result, motivation, creativity, discipline and enthusiasm for learning will all increase (Nurmaily, 2021). The aim of this research is to find out whether the Discovery Learning learning model can improve the mathematics learning outcomes of class VII students at SMP Negeri 5 Abiansemal. From the learning outcomes in the pre-cycle the achievement of learning completeness was 57.14% with an average value of 76.39 then in the first cycle it increased to 75% with an average value of 80.57 and in the second cycle it increased to 89.29% with an average -average value 84.79. Based on the results of cycle II, it can be seen that 89.29% of the total students have reached the KKM and 10.71% of the total students in the class have not reached the KKM. Based on all classroom action research activities, it can be concluded that through the application of the Discovery Learning learning model, it can improve the mathematics learning outcomes of class VII students at SMP Negeri 5 Abiansemal